Inovasi Manajemen Pengelolaan Sampah yang Berwawasan Lingkungan di Kota Pontianak berbasis Aplikasi - Ul Qadri; Riska Wahyuni; Lilis Listiyawati (Jurusan Akuntansi Politeknik Negeri Pontianak, 2020)
Waste management is problems are almost faced by all cities in Indonesia. Therefore, it is necessary to manage waste management with environmentally sound management in accordance with the mandate of Law No. 18 of 2008 on waste management. The aspect highlighted in the management of waste management in Pontianak City is the technical aspect of waste management and non-technical operations so that it can be known whether management of waste management is environmentally sound or unlike the bill of legislation. Pontianak City makes application-based innovations in managing garbage. The purpose of this research is to describe, analyse, and interpret, as well as recommendations on: (1) Waste management management covering technical aspects of operational and non-technical. (2) Environmentally sound and application-based waste management management. The methods used are qualitative descriptive, approach study studies, data sources derived from interviews with informant, observation and documentation. The data analysis technique used is interactive model analysis by reducing data, presenting data, drawing conclusions and verification.